A comparison of genome cohort participants' genetic knowledge and preferences to receive genetic results before and after a genetics workshop. Issue 11 (November 2018) - Yamamoto, Kayono; Shimizu, Atsushi; Aizawa, Fumie; Kawame, Hiroshi; Tokutomi, Tomoharu; Fukushima, Akimune
Abstract Several biobanks have begun returning genetic results to individuals, making the development of public genetic literacy an urgent task for their effective use. No research exists regarding the effects of genetic education on biobank participants, so we conducted genetics workshops with specialists, and surveyed differences in the participants' (n  = 112) preferences to receive their own genetic information by disease categories and their genetic knowledge using questionnaires before and after the workshops. Almost 90% of our participants were over 60 years old, which was similar to our previous preference research. The preference to receive five of the six categories of genetic information (lifestyle diseases, pharmacogenetics, adult-onset non-clinically actionable diseases, non-clinically actionable multifactorial diseases, and all genetic information) was slightly but significantly decreased after the genetics workshop. More participants preferred to receive genetic results regarding lifestyle diseases, pharmacogenetics, and adult-onset clinically actionable diseases after the workshop, while less participants preferred to receive information regarding adult-onset non-clinically actionable diseases, non-clinically actionable multifactorial diseases, and all genetic information. Total genetic knowledge scores significantly increased after the workshop (before: 11.89, after: 13.30, p  < 0.001). Our findings suggest that genetics workshops are useful to improve the genetic literacy of genome cohort participants.